Quasar feedback survey: multiphase outflows, turbulence, and evidence for feedback caused by low power radio jets inclined into the galaxy disc. Issue 2 (27th January 2022) - Girdhar, A; Harrison, C M; Mainieri, V; Bittner, A; Costa, T; Kharb, P; Mukherjee, D; Arrigoni Battaia, F; Alexander, D M; Calistro Rivera, G; Circosta, C; De Breuck, C; et al.
ABSTRACT: We present a study of a luminous, $z\, =\, 0.15$, type-2 quasar ($L_{[\rm O III]}$  = 10 42.8 erg s −1 ) from the Quasar Feedback Survey. It is classified as 'radio-quiet' ($L_{\mathrm{1.4\, GHz}}$  = 10 23.8  W Hz −1 ); however, radio imaging reveals ∼ 1 kpc low-power radio jets (Pjet  = 10 44  erg s −1 ) inclined into the plane of the galaxy disc. We combine MUSE and ALMA observations to map stellar kinematics and ionized and molecular gas properties. The jets are seen to drive galaxy-wide bi-conical turbulent outflows, reaching W 80  = 1000 – 1300 km s −1, in the ionized phase (traced via optical emission lines), which also have increased electron densities compared to the quiescent gas. The turbulent gas is driven perpendicular to the jet axis and is escaping along the galaxy minor axis, reaching 7.5 kpc on both sides. Traced via CO(3–2) emission, the turbulent material in molecular gas phase is one-third as spatially extended and has three times lower velocity-dispersion as compared to ionized gas. The jets are seen to be strongly interacting with the interstellar medium (ISM) through enhanced ionized emission and disturbed/depleted molecular gas at the jet termini. We see further evidence for jet-induced feedback through significantly higher stellar velocity-dispersion aligned, and co-spatial with, the jet axis ($\lt 5\, ^{\circ }$ ). We discuss possible negative and positive feedback scenarios arising due to the interaction of the low-power jets with the ISM in the context of recent jet–ISM interaction simulations, which qualitatively agree with our observations. We discuss how jet-induced feedback could be an important feedback mechanism even in bolometrically luminous 'radio-quiet' quasars.